Effects of slow deep breathing at high altitude on oxygen saturation, pulmonary and systemic hemodynamics. - Grzegorz Bilo (Public Library of Science (PLoS), 2012)
Slow deep breathing improves blood oxygenation (Sp(O2)) and affects hemodynamics in hypoxic patients. We investigated the ventilatory and hemodynamic effects of slow deep breathing in normal subjects at high altitude. We collected data in healthy lowlanders staying either at 4559 m for 2-3 days (Study A; N = 39) or at 5400 m for 12-16 days (Study B; N = 28). Study variables, including Sp(O2) and systemic and pulmonary arterial pressure, were assessed before, during and after 15 minutes of breathing at 6 breaths/min. At the end of slow breathing, an increase in Sp(O2) (Study A: from 80.2±7.7% to 89.5±8.2%; Study B: from 81.0±4.2% to 88.6±4.5; both p<0.001) and significant reductions in systemic and pulmonary arterial pressure occurred. This was associated with increased tidal volume and no changes in minute ventilation or pulmonary CO diffusion. Slow deep breathing improves ventilation efficiency for oxygen as shown by blood oxygenation increase, and it reduces systemic and pulmonary blood pressure at high altitude but does not change pulmonary gas diffusion.